Comparing teachers' assessments and national test results: Evidence from Sweden - Erica Lindahl (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This study compares results on national tests with teachers' assessment of student performance, by using Swedish data of grade 9 students (16 years old). I examine whether there are systematic differences correlated with gender and ethnic background. That is, if the relationship between school leaving certificates and national test results differs between girls and boys or between natives and non-natives. The results show that girls are more generously rewarded in teachers' assessment compared to test results in all three subjects studied. Non-native students are more generously rewarded in teachers' assessment compared to test results in two out of three subjects studied.
Keywords: I21; 330; School performance; gender; race; Allgemeinbildende Schule; Schüler; Bildungsniveau; Meinung; Geschlecht; Ethnische Gruppe; Schweden